2009
DOI: 10.1071/fp08187
|View full text |Cite
|
Sign up to set email alerts
|

ABA mediation of shoot cytokinin oxidase activity: assessing its impacts on cytokinin status and biomass allocation of nutrient-deprived durum wheat

Abstract: Although nutrient deprivation alters the concentrations of several plant hormones, the role of each in decreasing shoot-to-root ratio is not clear. A 10-fold dilution of the nutrient concentration supplied to hydroponically-grown 7-day-old durum wheat (Triticum turgidum L. ssp. durum Desf.) plants decreased shoot growth, shoot-to-root ratio and shoot and root cytokinin concentrations, increased shoot ABA concentration and shoot cytokinin oxidase activity, but had no effect on xylem sap ABA and cytokinin concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 38 publications
2
37
0
3
Order By: Relevance
“…CKs were eluted with 70% ethanol and the eluate evaporated to dryness and dissolved in a minimum of 80% ethanol. Thin-layer chromatography (TLC) was used for Z and ZR separation (Vysotskaya et al 2009). CKs were determined by an enzyme immunoassay method as described earlier (Kudoyarova et al 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CKs were eluted with 70% ethanol and the eluate evaporated to dryness and dissolved in a minimum of 80% ethanol. Thin-layer chromatography (TLC) was used for Z and ZR separation (Vysotskaya et al 2009). CKs were determined by an enzyme immunoassay method as described earlier (Kudoyarova et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…2015 and the references therein). A decrease in the cytokinin content under conditions of nutrient deficiency was accompanied by an increase in the root:shoot mass ratio (Vysotskaya et al 2009). …”
mentioning
confidence: 99%
“…Ethylene has also been associated with dehydration stress responses, though independently or in a complex relationship with ABA (Tanaka et al, 2005;Wilkinson and Davies, 2009). CK regulation of dehydration responses also involves cross-talk with other phytohormones including ABA Vysotskaya et al, 2009).…”
Section: Global Transcriptomic Responsesmentioning
confidence: 99%
“…Previous studies have shown that the relationship between ABA and cytokinins is complex. ABA suppressed cytokinin accumulation in roots and shoots of wheat (Triticum aestivum) and stimulated cytokinin oxidase activity, which presumably contributed to the decline in cytokinins (Vysotskaya et al, 2009). On the other hand, there is additional evidence that cytokinins may regulate ABA levels and response.…”
Section: Aba Was Not Found To Strongly Influence Sugar or Cytokinin Pmentioning
confidence: 99%